2020
DOI: 10.3390/chemosensors8040111
|View full text |Cite
|
Sign up to set email alerts
|

DFO@EVOH and 3,4-HP@EVOH: Towards New Polymeric Sorbents for Iron(III)

Abstract: The paper presents the synthesis and preliminary characterization of two novel solid-phase sorbents for iron(III), resulting from the functionalization of ethylene-vinyl alcohol copolymer (EVOH) with deferoxamine, DFO (DFO@EVOH), and a novel tripodal 3-hydroxy-4-pyridinone, named 3,4-HP (3,4-HP@EVOH). DFO and 3,4-HP have been covalently bonded to EVOH, using carbonyldiimidazole as a coupling agent. Before their use as Fe(III) sorbents, they were warm-pressed to obtain a thin film. Polymers have been characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The EVOH copolymer is a commercial plastic material commonly employed as a gas barrier layer in polylaminate packaging. , It is transparent, biocompatible, and insoluble in water, and it shows good mechanical and thermal properties and processability. , From a chemical point of view, it consists of a unique copolymer of ethylene and vinyl alcohol that can be easily functionalized with various molecules to obtain advanced materials for various applications. In Figure S1, the chemical structure of EVOH and the commercial EVOH beads are shown.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The EVOH copolymer is a commercial plastic material commonly employed as a gas barrier layer in polylaminate packaging. , It is transparent, biocompatible, and insoluble in water, and it shows good mechanical and thermal properties and processability. , From a chemical point of view, it consists of a unique copolymer of ethylene and vinyl alcohol that can be easily functionalized with various molecules to obtain advanced materials for various applications. In Figure S1, the chemical structure of EVOH and the commercial EVOH beads are shown.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…When an oxidized polymer (p-type) is exposed to a reducing agent (CO, NH 3 , CH 4 , H 2 , H 2 S, acetone, or ethanol), its resistivity rises; conversely, when the polymer’s surface reacts with an oxidizing agent (NOx, CO 2 , SO 2 , O 2 , or O 3 ), its resistivity reduces [ 50 , 51 ]. Korent et al [ 52 , 53 ] reported an inexpensive NH 3 sensor based on the polyaniline functionalization of a screen-printed electrode (SPE). The SPE was altered in this study by electrochemically polymerizing polyaniline in HCl.…”
Section: Synthetic Polymer-based Sensorsmentioning
confidence: 99%
“…Therefore, some recent research has been focused on the development of hexadentate (3,4-HP)-containing polymers. In particular, aimed to obtain an analytical sensor for Fe(III), a copolymer was obtained from ethylene-vinyl alcohol and a tripodal, 3-hydroxy-4-pyridinone-based chelator (KC18) affording a thin film named 3,4-HP@EVOH ( L34, Figure 9 ) [ 94 ]. Sorption isotherms demonstrated that the polymer is capable of sorbing Fe(III) even at low pH ~ 1.…”
Section: Polymeric and Dendrimeric Hydroxypyridinonesmentioning
confidence: 99%